English Learning Assistance in the Era Pandemic COVID-19 for Students in Mendiro - Semi Sukarni; Sudar Sudar; Junaedi Setiyono; Zulia Chasanah; Juita Triana (Universitas Muhammadiyah Purworejo, 2021)
This paper aims to provide information about English learning assistance in the era pandemic Covid-19 for students in Mendiro through the community service. This activity was done to respond the community’s need to minimize the problems of learning English which were appeared during Covid-19 pandemic. The participants of the activity were 25 students which consisted of primary schools, Junior High School and Senior High School. The main problem of the students were difficulties in understanding English lessons as they were lack of interaction with their teachers since they were study from home (BDR). They have limited strategies to do self study at home. To overcome the problems, a team of lecturers of English Language Education conducted a community service in Mendiro village, Ngombol subdistric of Purworejo. Through sharing of knowledge and strategies to learn English skills through internet media, the participants could get knowledge and took opportunity to practice their English. By adopting the strategies given by team of lecturers, the participants are expected to be able to learn English easier with more enjoyable and enjoy simple literary works such as short films, short stories, short stories videos and songs. Finally, they can obtain better English skills in the future